GSA ACTIVITIES - STUNTZ S (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Susan Stuntz to Bob Lewis regarding General Services Administration (GSA) activities. Details the activities taken on behalf of the tobacco industry to discourage the regulation of smoking in government buildings. Includes reports prepared by the Tobacco Institute and protests by labor unions, especially the American Federation of Government Employees (AFGE) union, which is particularly angry because they were consulted prior to the proposal yet none of their concerns were taken into consideration.